2000
DOI: 10.1159/000053205
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Growth Factors during Perinatal Life

Abstract: Pituitary growth hormone (GH) is present in early pregnancy in the fetal circulation. The concentrations are higher than ever found during life, due to an unrestrained, basal secretion. GH receptors develop around midpregnancy, when they are present in low concentrations, and there is a rapid increase during the first months of life. The function of fetal GH – characterized by a nearly complete GH resistance – is largely unclear: there is only a small effect on longitudinal growth, and the regulation of growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
1
29
1
1
Order By: Relevance
“…Nevertheless, the possibility of involvement of GH-dependent endocrine pathways cannot be ruled out. In fact, ghrelin expression in fetal lung reaches its peak at mid-gestation, when serum GH levels also reach maximal values (22). The presence of GH mRNA in the fetal rat lung during pseudoglandular stage, was recently documented (23), and it has been suggested that fetal GH can interact with GH receptors existent in fetal lung epithelium (24,25) and modulate lung growth by interfering with IGF activity while increasing IGFBP-2 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the possibility of involvement of GH-dependent endocrine pathways cannot be ruled out. In fact, ghrelin expression in fetal lung reaches its peak at mid-gestation, when serum GH levels also reach maximal values (22). The presence of GH mRNA in the fetal rat lung during pseudoglandular stage, was recently documented (23), and it has been suggested that fetal GH can interact with GH receptors existent in fetal lung epithelium (24,25) and modulate lung growth by interfering with IGF activity while increasing IGFBP-2 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there was no decrease in RI in cows from week 37 to week 39 of gestation [38]. The fall in RI represents an adaption to growing demands on gas exchange and transfer of nutrients and metabolites during the last trimester of gestation [36][37][38]. Structural changes in blood vessels of the human fetoplacental unit are associated with increased vascular elasticity and result in a reduction of vascular resistance [39].…”
Section: Analysis Of Sonographic Measurementsmentioning
confidence: 95%
“…A continuous decrease of 35% in the RI of both AUT occurred in cattle during the first 28 weeks of gestation, but no further decrease was noted at monthly measurements during the remainder of gestation [6]. Likewise, there was no decrease in RI in cows from week 37 to week 39 of gestation [38]. The fall in RI represents an adaption to growing demands on gas exchange and transfer of nutrients and metabolites during the last trimester of gestation [36][37][38].…”
Section: Analysis Of Sonographic Measurementsmentioning
confidence: 99%
“…Previous studies have shown that IGF-I has a more critical role than the other factors (56)(57)(58), and growth hormone is not an important regulator of IGF-I secretion during perinatal life (57,58). In addition, children with IGF-I gene deletion are characterized by severe prenatal and postnatal growth retardation (59).…”
Section: Insulin-like Growth Factor-i (Igf-i)mentioning
confidence: 99%